FRP Composites and their Using in the Construction of Bridges. (2016) - Sonnenschein, Robert; Gajdosova, Katarina; Holly, Ivan
Abstract: Traditional material for concrete reinforcement is steel. In recent times, non-metallic fibres have been intensively investigated and some of them used for construction of bridges. FRP composites are durable materials which are different from the steel reinforcement for their resistance to the electrochemical corrosion. With respect to steel, different mechanical behavior of non-metallic reinforcement, however, involves some drawbacks - namely the lack of thermal compatibility between concrete and FRP reinforcement. FRP composites belong among anisotropic materials. Their properties depend on the type, volume and alignment of the fibres, the matrix type, form and quality of the construction. The analysis of causes of failures on German bridges shows that reinforcement corrosion initiated by chlorides makes up 2/3 of all the failures recorded in the bridge construction. Corrosion of the reinforcement initiated by chlorides is the main cause of the loss of serviceability of bridge structures. In such an environment, fibre-reinforced polymer (FRP) reinforcement can fully replace the traditional steel reinforcement. The paper presents the mechanical properties and durability of different types of the FRP rebar's and their use in construction of bridges.